2014
DOI: 10.1093/nar/gku1076
|View full text |Cite
|
Sign up to set email alerts
|

APASdb: a database describing alternative poly(A) sites and selection of heterogeneous cleavage sites downstream of poly(A) signals

Abstract: Increasing amounts of genes have been shown to utilize alternative polyadenylation (APA) 3′-processing sites depending on the cell and tissue type and/or physiological and pathological conditions at the time of processing, and the construction of genome-wide database regarding APA is urgently needed for better understanding poly(A) site selection and APA-directed gene expression regulation for a given biology. Here we present a web-accessible database, named APASdb (http://mosas.sysu.edu.cn/utr), which can vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(71 citation statements)
references
References 32 publications
2
68
1
Order By: Relevance
“…Many experimental protocols to capture transcript 3 ′ ends and enable studies of the dynamics of polyadenylation have been developed (for review, see de Klerk et al 2014), and consequently, a few databases of 3 ′ end processing sites are available (Lee et al 2007;Derti et al 2012;You et al 2014). However, none of these databases has used the entire set of 3 ′ end sequencing data available to date, and thus, their coverage is limited.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Many experimental protocols to capture transcript 3 ′ ends and enable studies of the dynamics of polyadenylation have been developed (for review, see de Klerk et al 2014), and consequently, a few databases of 3 ′ end processing sites are available (Lee et al 2007;Derti et al 2012;You et al 2014). However, none of these databases has used the entire set of 3 ′ end sequencing data available to date, and thus, their coverage is limited.…”
Section: Discussionmentioning
confidence: 99%
“…By comparing the 3 ′ end processing sites from two recent genome-wide studies (Derti et al 2012;You et al 2014), we found that a substantial proportion was unique to one or the other of the two studies (Supplemental Table 1). This motivated us to develop a uniform and flexible processing pipeline that facilitates the incorporation of all published sequencing data sets, yielding a comprehensive set of high-confidence 3 ′ end processing sites.…”
Section: Preliminary Processing Ofmentioning
confidence: 99%
See 2 more Smart Citations
“…The relative positions of these CPA sites in the 3 ′ UTR of a gene and the sequence elements contained between them may result in the differential regulation of APA isoforms through RNA stability, translational efficiency, or subcellular localization (Sandberg et al 2008;Weill et al 2012). The realization that APA occurs in most genes, and thereby potentially regulates widespread gene expression, triggered a flurry of investigations to annotate APA profiles in different tissues and cellular states (Ozsolak et al 2010;Derti et al 2012;Lin et al 2012;You et al 2015). RNA-seq-based global analysis extended the proportion of human genes that contain multiple CPA sites to ∼70% and demonstrated that APA not only occurs throughout tissues but may also be evolutionarily conserved (Tian et al 2005;Derti et al 2012;Miura et al 2013).…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%